Development of Students' Religious Character Through Intimate Friendship - Husniah, Laila; Hamdanah, Hamdanah; Surawan, Surawan (Jayapangus Press, 2025)
Intimate friendship can have a significant impact on a person's religious character, both positively and negatively, depending on the dynamics of the relationship. Therefore, this study aims to determine the development of students' religious character through intimate friendship. The method used is qualitative with 10 students in grade XI, namely 5 students of BRL 1 and 5 students of XI BRL 2, using a phenomenological approach. Data collection was carried out through observation, interviews, and documentation. The results of the observation show the development of students' religious character through intimate friendship, that close friendship and mutual trust between students can play a role in helping the development of their religious character. Friends who support each other in terms of religious values ​​will help shape students' personalities to be better in terms of religion. The results of the study show that the development of students' religious character through intimate friendship at SMKN 2 Palangka Raya can be encouraged through intimate friendship. In the school environment, close friendship between students not only strengthens social ties, but also influences the formation of religious character. In addition, through close friendships, students feel more comfortable and confident in expressing their feelings, be it happiness, anxiety, or challenges faced in everyday life. In this supportive environment, they can more freely discuss various issues, including moral dilemmas, religious understanding, or even challenges in practicing Islamic values ​​in real life. Through open discussions and sharing experiences, students not only gain new perspectives, but also feel supported in their spiritual journey. For example, when a student has difficulty maintaining consistency in worship, his close friends can provide motivation or reminders in a more personal and empathetic way.